1992
DOI: 10.1113/jphysiol.1992.sp019270
|View full text |Cite
|
Sign up to set email alerts
|

Sulphydryl reagents trigger Ca2+ release from the sarcoplasmic reticulum of skinned rabbit psoas fibres.

Abstract: SUMMARY1. By analogy with studies on sarcoplasmic reticulum (SR) vesicles, Ca2+ release induced by heavy metals and mercaptans (e.g. cysteine) was investigated in rabbit skinned psoas fibres through measurements of isometric tension.2. Heavy metals (at 2-5 /tM) elicited phasic contractions by triggering Ca2+ release from the SR and had the following order of potency: Hg2+ > Cu2+ > Cd2+ > Ag+ > Ni2+. Higher concentrations produced tonic contractions due to maintained high Ca2+ permeability of SR membranes.3. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 37 publications
(45 reference statements)
3
49
1
Order By: Relevance
“…It has been demonstrated that a number of sulfhydryl-oxidizing reagents activate RyR channels (40,41,43). Sulfhydrylreducing reagents such as glutathione and DTT have been shown to reduce the RyR channel activity (39,42).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that a number of sulfhydryl-oxidizing reagents activate RyR channels (40,41,43). Sulfhydrylreducing reagents such as glutathione and DTT have been shown to reduce the RyR channel activity (39,42).…”
Section: Discussionmentioning
confidence: 99%
“…This observation initially suggests that the oxidant-activated channel may not require the presence of an intracellular messenger to remain active. Ca2+ release channels from the sarcoplasmic reticulum of skeletal muscle are activated by the oxidation of critical thiol-containing residues (Salama, Abramson & Pike, 1992). Further, thiol oxidation has been shown to modulate the activity of non-selective channels in adipocytes (Koivisto, Siemen & Nedergaard, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been proposed that endogenous sulfhydryl (SH) groups present on the RYR protein may be responsible for regulating the gating of the SR Ca 2ϩ -release channel (1,111,112). It has been demonstrated that oxidation of the SH groups stimulates SR Ca 2ϩ release in vesicle experiments (2) and muscle fibers (112).…”
Section: Current Theories In Eccmentioning
confidence: 99%
“…It has been demonstrated that oxidation of the SH groups stimulates SR Ca 2ϩ release in vesicle experiments (2) and muscle fibers (112). Whereas no clear role for the SH regulation has been established, it remains a viable mechanism to modulate channel gating.…”
Section: Current Theories In Eccmentioning
confidence: 99%